2023
DOI: 10.3390/educsci13020110
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Mobile Instant Messaging in English Language Teaching: The Case of South Korea

Abstract: While learning management systems and video conferencing platforms have become a pivotal means for implementing emergency remote learning during the COVID-19 pandemic, the integration of mobile technologies into online teaching has been largely recommended in order to create an interactive educational environment. Focusing on the case of an English Language Program in South Korea, this study investigates the actual use of mobile instant messaging (MIM) applications as a learning aid in online language classroo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…Table 5 below displays the language skills focused on in utilising MIM in English language teaching. Chung & Choi (2023) Based on the data obtained in Table 5 it is evident that most of the implementation of MIM in English language teaching are based on speaking skills followed by writing skills and vocabulary. There are a total of 9 articles that discusses speaking as a skill that is focused in their research (Albogami & Algethami, 2022;Fitriani, 2020;Garcia-Ponce et al, 2023;Imamyartha et al, 2022;Karthika & Selvam, 2022;Makoe & Shandu, 2019;Martínez & Appel, 2020;Martínez & Appel, 2022;Noni & Basri, 2019).…”
Section: Rq 1: What Are the Types Of Mobile Instant Messages Used In ...mentioning
confidence: 96%
See 4 more Smart Citations
“…Table 5 below displays the language skills focused on in utilising MIM in English language teaching. Chung & Choi (2023) Based on the data obtained in Table 5 it is evident that most of the implementation of MIM in English language teaching are based on speaking skills followed by writing skills and vocabulary. There are a total of 9 articles that discusses speaking as a skill that is focused in their research (Albogami & Algethami, 2022;Fitriani, 2020;Garcia-Ponce et al, 2023;Imamyartha et al, 2022;Karthika & Selvam, 2022;Makoe & Shandu, 2019;Martínez & Appel, 2020;Martínez & Appel, 2022;Noni & Basri, 2019).…”
Section: Rq 1: What Are the Types Of Mobile Instant Messages Used In ...mentioning
confidence: 96%
“…The findings are presented as below. Ghorbani & Ebadi (2020) Kakao Talk Chung & Choi (2023) Based on Table 4, a total of 18 research articles demonstrated that WhatsApp is the favoured MIM used in teaching English (Alamer et al, 2023;Albogami & Algethami, 2022;Almogheerah, 2021;Alubthane & ALYoussef, 2021;Arifani et al, 2020;Cetinkaya & Sutcu, 2019;Cetinkaya, 2020;Fitriani, 2020;Garcia-Ponce et al, 2023;Imamyartha et al, 2022;Karthika & Selvam, 2022;Makoe & Shandu , 2019;Makoza & Bagui, 2022;Martínez & Appel, 2020;Martínez & Appel, 2022;Menggo et al, 2023;Noni & Basri, 2019;Suhaimi et al, 2019). It is supported by Alamer et al (2023) that WhatsApp is indeed a great tool in helping ESL learners to learn and master all the language skills.…”
Section: Rq 1: What Are the Types Of Mobile Instant Messages Used In ...mentioning
confidence: 99%
See 3 more Smart Citations